Systematic Review Therapeutic Positions Are Able To Improve The Hemodynamic Status Of Acute Decompensated Heart Failure (Adhf) Patients - Rahmasari, Ikrima; Irawan AM, Ady; Najib Hassan, Ahmad; Andita Febriana, Andita (LPPM Universitas Duta Bangsa Surakarta, 2024)
Background: Acute Decompensated Heart Failure (ADHF) is acute heart failure which is defined as a rapid onset of symptoms due to abnormal heart function. These dysfunctions include systolic and diastolic dysfunction, heart rhythm abnormalities, or preload and afterload imbalances. ADHF is a new attack without previous heart defects, or is decompensation of chronic heart failure (Chronic Heart Failure) that has been experienced previously. ADHF occurs when cardiac output cannot meet the body's metabolic needs. Objective: in this study, namely to determine the results of a literature review of the effect of therapeutic positions on hemodynamic status in ADHF patients. The method in this research is a literature review method using a literature search strategy through online media which includes searching on Google Scholar, PubMed, Research Gate, Elsevier, NCBI. Results: Based on the results of the literature review, all studies (4 studies) reviewed showed results of improvement in hemodynamic status, namely respiratory frequency, oxygen saturation (SaO2), blood pressure, heat rate, and CRT in ADHF patients who were given therapeutic position intervention: semi fowlershows increased oxygen saturation, decreased shortness of breath, stable blood pressure, hate rate, and respiratory rate. Conclusion: The therapeutic position, namely the semi fowler position, has an effect on improving the hemodynamic status of ADHF patients